2019
DOI: 10.3390/nu11061397
|View full text |Cite
|
Sign up to set email alerts
|

Using the Pleiotropic Characteristics of Curcumin to Validate the Potential Application of a Novel Gene Expression Screening Platform

Abstract: Curcumin is a polyphenol derived from curcumin longa that exhibits anticancer and anti-inflammatory properties. The consumption of foods at supernutritional levels to obtain health benefits may paradoxically result in negative health outcomes. In the present study, multiple targeting characteristics of curcumin were analyzed using our gene expression screening system, which utilized the gene expression signatures of curcumin from human hepatocellular carcinoma and colorectal cancer cells to query gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Intersection of results from both cell lines revealed that seven compounds (e.g., menadione and angiogenesis inhibitor; Figure 3D) and two PCLs (e.g., NF-κB pathway inhibitors; Figure 3B) shared common functions with conventional curcumin. In summary, formulated curcumin was similar to conventional curcumin, and both functioned as, for example, NF-κB pathway inhibitors, which is consistent with previous studies [33]. We intersected two sample groups to identify common PCL/compound classes between formulated curcumin treatment of HT29 cells and formulated curcumin treatment of HepG2 cells.…”
Section: Gene Expression Analysis Of Formulated Curcumin and Predictisupporting
confidence: 84%
“…Intersection of results from both cell lines revealed that seven compounds (e.g., menadione and angiogenesis inhibitor; Figure 3D) and two PCLs (e.g., NF-κB pathway inhibitors; Figure 3B) shared common functions with conventional curcumin. In summary, formulated curcumin was similar to conventional curcumin, and both functioned as, for example, NF-κB pathway inhibitors, which is consistent with previous studies [33]. We intersected two sample groups to identify common PCL/compound classes between formulated curcumin treatment of HT29 cells and formulated curcumin treatment of HepG2 cells.…”
Section: Gene Expression Analysis Of Formulated Curcumin and Predictisupporting
confidence: 84%
“…PIK3R1 is considered a tumour suppressor associated with increased cell proliferation and invasion, and decreased cell apoptosis [ 53 , 54 ]. Curcumin effectively inhibits NF-κB activity by blocking PIK3R1 in the NF-κB cascade pathway of CD4-T cell receptor signalling, thereby triggering cellular G2/M phase blockade and apoptotic processes [ 55 ]. It also mediates apoptosis of PCa cells by inducing the expression of PIK3R1 [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin shows an elevated degree of pleiotropy, which is responsible for the heterogeneous responses observed following its administration. Furthermore, curcumin triggers the downregulation of many genes involved in the inflammatory response, displaying anti-inflammatory activity, as well as the downregulation of anti-apoptotic proteins [ 20 , 21 ]. Lastly, it has been related to the HAT p300 inhibition and to a reduction in CDK1 transcription, which probably underlies the G2/M arrest observed in cancer cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that some molecules display pronounced anti-cancer activity by triggering senescence in cancer cells. For example, the natural polyphenol curcumin, derived from Curcuma longa , has been shown to induce senescence in HCT116 cancer cells by causing cell-cycle arrest in the G2/M phase [ 18 , 19 , 20 , 21 ]. Herein, we investigate the mechanism/s underlying curcumin-mediated senescence, confirming its more specific action against cancer cells.…”
Section: Introductionmentioning
confidence: 99%